A method for evaluating damage sensitivity of a resin-based composite material based on polydopamine-coated carboxylated carbon nanotubes

CN123017282APending Publication Date: 2026-10-30BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611092643.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但单纯羧基化处理仍难以同时兼顾分散稳定性与界面结合强度

Benefits of technology

[0056]结合上述的所有技术方案,本发明所具备的优点及显著效果为:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017282A_ABST
    Figure CN123017282A_ABST
Patent Text Reader

Abstract

The application provides a kind of based on polydopamine coated carboxylated carbon nanotube enhanced resin matrix composite damage sensitivity evaluation method, the method is prepared by CNTs purification, carboxylation and PDA coating polydopamine coated carboxylated carbon nanotube, and it is added to resin matrix to obtain different content composite, and the dispersion of reinforcing phase and the adhesion of interface are characterized by combining mechanical test, nondestructive testing, image analysis and scanning probe microscopy.Further, a micro model containing resin, polydopamine coated carboxylated carbon nanotube and interface phase is established, and a three-dimensional damage constitutive model is constructed by combining ABAQUS software and FORTRAN user subroutine, which realizes the initial determination of composite damage, stiffness degradation analysis and damage failure simulation. By combining the experimental results with the numerical simulation results, the damage initiation behavior, stiffness degradation rule and crack propagation process of the composite under different polydopamine coated carboxylated carbon nanotube dispersion states and content conditions are quantitatively compared and analyzed, and the distribution form of the reinforcing phase that is beneficial to improve the crack propagation resistance of the material is determined, which provides a method basis for the damage resistance optimization design of resin matrix composite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of resin-based composite material modification and finite element simulation, specifically to a method for evaluating the damage sensitivity of resin-based composite materials reinforced with polydopamine-coated carboxylated carbon nanotubes. Background Technology

[0002] Resin-based composite materials are widely used in aerospace, wind power, and high-end manufacturing due to their high specific strength, lightweight, good corrosion resistance, and designability. However, during service, resin-based composite materials are prone to problems such as microcrack initiation, pore propagation, interfacial debonding, and localized damage accumulation. These micro-damages are often difficult to identify directly through macroscopic means in the initial stage, but they continuously weaken the overall load-bearing capacity of the material, eventually leading to sudden failure of the resin-based composite material. Therefore, improving the low damage sensitivity characteristics of resin-based composite materials and establishing analytical methods that take into account both microstructural evolution and macroscopic mechanical response have become important research directions in the field of composite materials.

[0003] In recent years, carbon nanotubes (CNTs) have become important reinforcing materials for improving the mechanical and interfacial properties of resin-based composites due to their excellent mechanical properties, high aspect ratio, and good surface modification potential. For example, the patent "A Reinforced and Toughened Carbon Nanotube-Modified Polypropylene Resin and Its Fiber Composite Material" improves the mechanical properties of polymer composites by introducing carbon nanotubes into a polypropylene matrix. However, untreated carbon nanotubes have strong surface inertness, are prone to agglomeration, have poor dispersion in the resin matrix, and limited interfacial compatibility with the matrix, thus making it difficult to fully realize their reinforcing and toughening effects. On the other hand, traditional material performance research relies heavily on macroscopic experimental testing, which can obtain basic indicators such as strength and modulus, but it is difficult to reveal key mechanisms such as the distribution of reinforcing phases, interfacial damage evolution, and crack propagation paths at the microscale. The patent "A Prediction and Simulation System for the Reinforcing Effect of Single-Walled Carbon Nanotube Powder" introduces single-walled carbon nanotubes into the matrix material in powder form and quantitatively evaluates the reinforcing potential of carbon nanotubes through multi-scale modeling and numerical simulation. However, existing numerical simulation methods for handling nano-reinforced resin composites generally suffer from problems such as oversimplification of microstructure, insufficient description of interface properties, and inadequate damage constitutive models, making it difficult to accurately reflect the micromechanical behavior of actual materials. Therefore, there is an urgent need to develop a method that organically combines material preparation, experimental characterization, microscopic modeling, and damage simulation to achieve a systematic study of the low damage sensitivity characteristics and mechanical behavior of polydopamine-coated carboxylated carbon nanotube-reinforced resin composites.

[0004] Based on this, this invention proposes a method for evaluating the damage sensitivity of resin-based composite materials reinforced with polydopamine-coated carboxylated carbon nanotubes. To improve the surface activity of carbon nanotubes, acidification and oxidation methods are often used to introduce oxygen-containing functional groups such as carboxyl groups onto their surface, thereby enhancing their reactivity and dispersibility. However, simple carboxylation treatment still struggles to simultaneously achieve both dispersion stability and interfacial bonding strength. Dopamine, due to its excellent biomimetic adhesion properties, can self-polymerize under weakly alkaline conditions to form a polydopamine coating, thus constructing a functionalized interfacial layer on the carbon nanotube surface. This interfacial layer not only improves the dispersion of carbon nanotubes in the resin but also enhances the interfacial adhesion between the nano-reinforcement and the resin matrix, thereby improving the toughening effect and damage resistance of the material. Therefore, by introducing dopamine-coated carboxylated carbon nanotubes (polydopamine-coated carboxylated carbon nanotubes), the surface functionalization of carbon nanotubes can be achieved, effectively improving their dispersibility and interfacial bonding performance in the resin matrix, providing a new approach to enhancing the low damage sensitivity characteristics of composite materials. Furthermore, by combining microscopic modeling and three-dimensional damage simulation, we conducted a comparative analysis of the quantitative effects of different polydopamine-coated carboxylated carbon nanotube contents and dispersion states on the damage initiation, stiffness degradation, and crack propagation processes of composite materials, providing new methodological support for the design of crack propagation resistance of resin-based composite materials. Summary of the Invention

[0005] This invention provides a method for evaluating the damage sensitivity of resin-based composite materials reinforced with polydopamine-coated carboxylated carbon nanotubes (PDCNTs). First, carbon nanotubes are purified, carboxylated, and modified with dopamine to prepare PDCNTs, thereby improving their dispersion uniformity and interfacial reinforcement in the resin matrix. Subsequently, PDCNTs are introduced into the resin matrix to prepare PDCNT / EP composite material systems with different contents. Mechanical parameters, reinforcing phase dispersion characteristics, and interfacial adhesion properties of the composite materials are characterized using mechanical property testing, non-destructive testing, image analysis, and scanning probe microscopy. Based on this, a microscopic model is established, comprising the resin matrix, reinforcing phases with different contents of PDCNTs, and interfacial phases. A three-dimensional damage constitutive model is constructed using ABAQUS software and FORTRAN user subroutines, enabling initial damage assessment, stiffness degradation analysis, and crack propagation simulation of the composite materials. By combining experimental characterization results with numerical simulation results, a quantitative comparative analysis was conducted on the damage initiation behavior, stiffness degradation law and crack propagation process of composite materials with different polydopamine-coated carboxylated carbon nanotube contents and dispersion states. The distribution form of the reinforcing phase that is conducive to improving the crack propagation resistance of the material was determined, providing a methodological basis for the damage-resistant optimization design of resin-based composite materials.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] A method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites, characterized by comprising the following steps:

[0008] (1) Preparation of polydopamine-coated carboxylated carbon nanotubes

[0009] (a) Purification of CNTs: CNTs were placed in a muffle furnace and calcined at 480-550°C for 0.5-1 hour. After natural cooling, the calcined CNTs were mixed with 2.5-3.0 mol / L nitric acid solution and stirred at 90-100°C for 2-3 hours. After natural cooling, the mixture was centrifuged. The product was washed 3-5 times with deionized water and dried in a vacuum drying oven at 40-50°C for 10-15 hours to obtain purified CNTs.

[0010] (b) Preparation of CNT-COOH: Under ventilation conditions, 150 mL of concentrated sulfuric acid was slowly added to 50 mL of concentrated nitric acid while stirring with a glass rod to obtain a mixed acid solution. The mixed acid solution was transferred to a 100 mL round-bottom flask equipped with a magnetic stirrer, reflux condenser, and tail gas recovery device. 1.0 g of purified CNTs was weighed and slowly added to the mixed acid solution through a long-necked funnel. After ultrasonic dispersion for 30 minutes, the flask was placed in an oil bath and refluxed at 50-60°C for 3-4 hours. Subsequently, the mixture was washed 3-4 times by centrifugation with deionized water and dried in a vacuum drying oven at 40-50°C for 10-15 hours to obtain CNT-COOH.

[0011] (c) Preparation of polydopamine-coated carboxylated carbon nanotubes: Weigh 100-150 mg of Tris base, dissolve it in 80-100 mL of deionized water, slowly adjust the pH to 8.5 with 1 M HCl, and bring the volume to 100 mL to obtain Tris-HCl buffer; weigh 100 mg of CNT-COOH and add it to 50-80 mL of Tris-HCl buffer, sonicate for 30 minutes to obtain a uniform black dispersion; weigh 100 mg of dopamine hydrochloride and add it to the black dispersion; perform PDA coating reaction by magnetic stirring at 15-30℃ for 6-8 hours; after the reaction, transfer the mixture to a centrifuge tube and centrifuge at 8000-10000 rpm for 10-15 minutes. After min, the supernatant is discarded. The precipitate is ultrasonically dispersed with deionized water and centrifuged repeatedly 3-5 times until the supernatant is clear. The precipitate is collected and placed in a vacuum drying oven at 40-50°C for 10-15 h. After grinding, polydopamine-coated carboxylated carbon nanotubes are obtained.

[0012] (2) Configuring a polydopamine-coated carboxylated carbon nanotube / EP system

[0013] Weigh the polydopamine-coated carboxylated carbon nanotubes prepared in step (1), add them to the acetone solution according to the preset addition amount, stir for 5 to 10 min under mechanical stirring at 200 to 500 r / min, and then perform ultrasonic dispersion treatment for 30 to 60 min. Subsequently, add the resin matrix and curing agent to the above dispersion in sequence, and continue stirring for 10 to 20 min under the conditions of 25 to 80 ℃ and 200 to 500 r / min. Remove the acetone by vacuum to obtain resin systems with different polydopamine-coated carboxylated carbon nanotube contents. As a control, prepare a pure EP system containing only resin matrix and curing agent at the same time. Finally, place each group of resin systems in an oven and cure according to the step curing regime to obtain polydopamine-coated carboxylated carbon nanotube / EP composite material samples with different polydopamine-coated carboxylated carbon nanotube distribution characteristics.

[0014] (3) Performance characterization of polydopamine-coated carboxylated carbon nanotubes / EP

[0015] The microstructure of polydopamine-coated carboxylated carbon nanotube / EP composite materials with different polydopamine-coated carboxylated carbon nanotube contents prepared in step (2) and the control samples of pure EP system were characterized by non-destructive testing. Information such as particle size, distribution position, aggregation degree and orientation characteristics of polydopamine-coated carboxylated carbon nanotubes in resin matrix were obtained, and their dispersion uniformity was quantitatively evaluated by image analysis method. At the same time, mechanical property tests were performed on each group of samples to obtain the corresponding mechanical property parameters. Furthermore, scanning probe microscopy was used to determine the adhesion performance of polydopamine-coated carboxylated carbon nanotubes at the interface with EP matrix, providing a parameter basis for subsequent microscopic model construction and damage analysis.

[0016] (4) Construction of the microstructure model of polydopamine-coated carboxylated carbon nanotubes / EP

[0017] Based on the actual size and spatial distribution characteristics of polydopamine-coated carboxylated carbon nanotubes obtained in step (3), a program was written to realize the microscopic modeling of polydopamine-coated carboxylated carbon nanotubes in the resin matrix. Uniform dispersion microscopic models and agglomeration dispersion microscopic models under different polydopamine-coated carboxylated carbon nanotube contents were established respectively. A microscopic model containing resin, polydopamine-coated carboxylated carbon nanotubes and polydopamine-coated carboxylated carbon nanotubes / EP interface was created in ABAQUS software.

[0018] (5) Material property assignment and model setup

[0019] Based on the mechanical property parameters of the control system obtained in step 3), the material properties of the resin components in the micro model are assigned. Based on the adhesion properties of the polydopamine-coated carboxylated carbon nanotubes and the EP interface obtained in step 3), the material properties of the polydopamine-coated carboxylated carbon nanotubes / EP interface in the micro model are assigned. The micro model created in step (4) is meshed, and the constraints, boundary conditions and loads of the micro model are set.

[0020] (6) Construction of three-dimensional damage constitutive model

[0021] Based on the three-dimensional failure criteria and fracture energy evolution method, a FORTRAN user-defined UMAT subroutine was written to construct a three-dimensional damage constitutive model of resin, polydopamine-coated carboxylated carbon nanotubes and interface phases, so as to realize the initial damage determination, stiffness degradation and crack propagation analysis of polydopamine-coated carboxylated carbon nanotubes / EP.

[0022] (7) Simulation analysis and result verification

[0023] The tensile strength and tensile modulus of the micro-models established under different polydopamine-coated carboxylated carbon nanotube contents and dispersion degrees were analyzed and compared with the tensile results obtained from experimental tests. This verifies the influence of the dispersion state and content of polydopamine-coated carboxylated carbon nanotubes on the damage sensitivity characteristics and crack propagation behavior of the resin system. Furthermore, the damage evolution process and failure mode of the material under different conditions were analyzed.

[0024] The purification and calcination temperature of CNTs in step (1) is determined by thermogravimetric analysis. Thermogravimetric analysis is performed on CNTs in an air atmosphere to obtain the TGA curve. The first derivative of the TGA curve is performed based on temperature to determine the temperature window between the oxidation weight loss range of amorphous carbon doped in CNTs and the decomposition temperature of CNTs. The purification and calcination temperature range of CNTs is determined to be 480-550℃, preferably 500-530℃.

[0025] The mixed acid solution in step (1) consists of concentrated sulfuric acid and concentrated nitric acid, wherein the mass fraction of concentrated sulfuric acid is 95%-98%, the mass fraction of concentrated nitric acid is 65%-68%, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 5:2-5:3.

[0026] The resin matrix described in step (2) consists of a main resin and a diluent. The resin matrix is ​​liquid at 10-30°C. The main resin is preferably a compound of one or more of the following: glycidyl ethers, glycidyl esters, glycidyl amines, hydantoin epoxy resin, vinyl resin, phenolic resin, bismaleimide resin, cyanate ester resin, polyimide resin, and polyurethane. The diluent is preferably alkylene glycidyl ether, 1,6-hexanediol diglycidyl ether, butyl glycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, phenyl glycidyl ether, benzyl glycidyl ether, and polypropylene. The curing agent is a compound of one or more of diglycidyl glycol diglycidyl ethers, wherein the mass ratio of the main resin to the diluent is 100:10-30; the curing agent is liquid at 10-30°C, preferably a compound of one or more of phthalic anhydride, dimethylthiotoluene diamine, isophorone diamine, diethyltoluene diamine, triethylenetetramine, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and methylnadic anhydride, wherein the mass ratio of the resin matrix, the curing agent, and the polydopamine-coated carboxylated carbon nanotubes is 100:10-40:0.1-0.8.

[0027] The stepped curing process described in step (2) includes: a) first heating to 60-100 ℃ and holding for 0.5-2 h; b) then heating to 100-140 ℃ and holding for 1-5 h; c) finally heating to 150-180 ℃ and holding for 1-5 h.

[0028] The mechanical parameters mentioned in step (3) include the tensile strength, tensile modulus, elongation at break, Poisson's ratio, fracture toughness and other mechanical property tests of polydopamine-coated carboxylated carbon nanotubes / EP, and the stress-strain curve of polydopamine-coated carboxylated carbon nanotubes / EP is obtained.

[0029] The non-destructive testing in step (3) includes metallographic microscopy, transmission electron microscopy, scanning electron microscopy, atomic force microscopy, and X-ray microcomputed tomography observation of the cross-section of polydopamine-coated carboxylated carbon nanotubes / EP, and metallographic microscopy, transmission electron microscopy, scanning electron microscopy, and X-ray microcomputed tomography observation of the tensile fracture surface of polydopamine-coated carboxylated carbon nanotubes / EP; the image analysis technology includes depth-of-field rendering, Avizo rendering, etc.; the particle size and dispersion state include the length and diameter of polydopamine-coated carboxylated carbon nanotubes, as well as their spatial distribution, volume fraction, and aggregation state in polydopamine-coated carboxylated carbon nanotubes / EP.

[0030] In the microscopic model described in step (4), with the resin matrix as a reference, at least five groups of polydopamine-coated carboxylated carbon nanotubes are set to have a dispersion mass fraction of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, and 0.8%, and the microscopic distribution of polydopamine-coated carboxylated carbon nanotubes in the resin matrix under different mass fraction conditions is modeled by writing a program.

[0031] In step (5), the preferred mesh type for the resin in the microscopic model is C3D8 or C3D8R; the preferred mesh types for polydopamine-coated carboxylated carbon nanotubes are C3D8, C3D8R, C3D4, and C3D6; the polydopamine-coated carboxylated carbon nanotube / EP interface is characterized by zero-thickness cohesive units, thin-layer interface units, or equivalent interface layers to represent the interface damage evolution behavior between the polydopamine-coated carboxylated carbon nanotubes and the resin matrix. The preferred interface layer is COH3D8 mesh type. The microscopic model contains 1,000-300,000 units and 50,000-800,000 nodes.

[0032] The constraints, boundary conditions and loads mentioned in step (5) include setting a completely fixed constraint on one side of the micro model, i.e., Ux,y,z = δx,y,z = 0, while applying a uniaxial tensile displacement load on the other side.

[0033] The three-dimensional failure criteria mentioned in step (6) include one or more of the maximum strain criterion, maximum stress criterion, secondary stress criterion, and linear evolution methods based on the definition of fracture energy. The initial failure in the polydopamine-coated carboxylated carbon nanotube / EP model is defined by the maximum stress criterion and the maximum strain criterion.

[0034] The expression for the maximum strain criterion is as follows:

[0035]

[0036] Failure occurs if any of the conditions are met. If the material is considered isotropic, it can be further simplified to:

[0037] or

[0038] in The principal strains represent the three principal directions of the material. This represents the ultimate tensile strain in the corresponding direction. This represents the ultimate compressive strain in the corresponding direction. Represents the maximum principal strain. Represents the minimum principal strain. Represents the ultimate tensile strain of a material. Represents the ultimate compressive strain of the material;

[0039] The maximum stress criterion is expressed as follows:

[0040]

[0041] Failure occurs if any of the conditions are met. If the material is considered isotropic, it can be further simplified to:

[0042] or

[0043] in Represents the three principal stresses of the material. Represents the ultimate tensile strength in the three principal directions. Represents the ultimate compressive strength in the three principal directions. Represents the maximum principal stress. Represents the minimum principal stress. Represents the ultimate tensile strength of a material. Represents the ultimate compressive strength of the material;

[0044] A secondary stress criterion is used to define the crack initiation criterion in the crack propagation region of the polydopamine-coated carboxylated carbon nanotube / EP model. The principal stress form of the secondary stress criterion is expressed as follows:

[0045]

[0046] The failure condition is:

[0047]

[0048] The stress component form of the secondary stress criterion is expressed as follows:

[0049]

[0050] in, Represents the Von Mises equivalent stress. Represents the three principal stresses of the material. Representing three normal stress components, Representing three shear stress components, Represents the yield strength of the material;

[0051] A linear evolution method based on the definition of fracture energy is used to define the crack propagation evolution law in the crack propagation region of the polydopamine-coated carboxylated carbon nanotube / EP model, wherein the criterion for crack propagation is:

[0052]

[0053] Where G is the energy release rate per unit crack surface. G is the energy release rate per unit crack area. C It is the critical fracture energy of the material.

[0054] The custom UMAT subroutine described in step (6) compiles a performance degradation program for polydopamine-coated carboxylated carbon nanotubes / EP based on the selected failure criteria and performance degradation model. It saves the material performance parameters and failure coefficients calculated in each step as state variables. It comprehensively considers various damage mechanisms of polydopamine-coated carboxylated carbon nanotubes during uniaxial tensile testing, including micro-damage modes such as resin matrix cracking and debonding of polydopamine-coated carboxylated carbon nanotubes from the resin. It compares the tensile strength, tensile modulus, crack initiation location, crack propagation path, and damage failure modes obtained from the simulation with the experimental results to evaluate the effects of polydopamine-coated carboxylated carbon nanotube content and dispersion state on the low damage sensitivity characteristics, interface toughening effect, and mechanical property improvement of the resin composite material.

[0055] Invention Effects

[0056] Combining all the above technical solutions, the advantages and significant effects of this invention are as follows:

[0057] (1) This invention effectively removes impurities and amorphous carbon from the original CNTs by calcining, purifying, carboxylating, and coating them with PDA, thereby improving their surface activity and reactivity. The PDA coating layer can significantly improve the dispersion uniformity of CNT-COOH in epoxy resin and enhance its interfacial adhesion with the resin matrix, thus achieving a synergistic improvement in phase dispersion and interfacial performance.

[0058] (2) By introducing polydopamine-coated carboxylated carbon nanotubes, the present invention can effectively inhibit the initiation and propagation of microcracks inside the resin matrix, reduce the phenomenon of interface debonding and local stress concentration, and enable the composite material to maintain higher structural stability and load-bearing capacity in the low load or initial damage stage, thereby improving the low damage sensitivity characteristics of the resin composite material.

[0059] (3) This invention establishes a research path that combines experimental characterization with microscopic simulation. Microstructural parameters and interface performance parameters are obtained through non-destructive testing, image analysis, and scanning probe microscopy, accurately characterizing the spatial distribution and dispersion state of polydopamine-coated carboxylated carbon nanotubes in EP. These parameters are then introduced into the finite element model, realizing an effective mapping of material experimental results to numerical simulation parameters, thus improving the realism and credibility of the simulation analysis.

[0060] (4) This invention constructs a three-dimensional damage constitutive model applicable to polydopamine-coated carboxylated carbon nanotube reinforced resin systems. Based on the three-dimensional failure criterion and fracture energy theory, a FORTRAN user-defined UMAT subroutine was written to simulate the damage evolution process of the resin phase, reinforcing phase, and interface. It can quantitatively compare and analyze the damage initiation behavior, stiffness degradation law, and crack propagation process of composite materials under different polydopamine-coated carboxylated carbon nanotube dispersion states and contents, determine the reinforcing phase distribution form that is conducive to improving the crack propagation resistance of the material, and guide the optimization design of the damage resistance performance of resin-based composite materials. Attached Figure Description

[0061] Figure 1 This is a flowchart of a method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites, as described in this patent.

[0062] Figure 2 The transmission electron microscope image of the polydopamine-coated carboxylated carbon nanotubes prepared in Example 1 is used to characterize the morphology and dispersion state of the carbon nanotubes after PDA coating.

[0063] Figure 3 The image shows a scanning electron microscope (SEM) image of the tensile fracture surface of polydopamine-coated carboxylated carbon nanotubes / EP in Example 1, used to observe the interface bonding between the reinforcing phase and the resin matrix and the fracture morphology.

[0064] Figure 4 This is a schematic diagram showing the construction, mesh generation, and constraint boundary conditions and load settings of the polydopamine-coated carboxylated carbon nanotube / EP micromodel in Example 1.

[0065] Figure 5 The image shows the stress distribution cloud map of the polydopamine-coated carboxylated carbon nanotube / EP micromodel in Example 1 under tensile load, used to illustrate the influence of the dispersion state of the reinforcing phase on stress transmission and damage sensitivity. Detailed Implementation

[0066] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but the present invention is not limited to these embodiments.

[0067] Example 1

[0068] (1) Preparation of polydopamine-coated carboxylated carbon nanotubes

[0069] First, thermogravimetric analysis (TGA) was performed on the raw CNTs under air atmosphere to obtain TGA curves, and temperature-based first-order derivative analysis was performed on the TGA curves. Based on the temperature window between the amorphous carbon oxidation weight loss region and the obvious decomposition region of the CNT bulk, the purification calcination temperature was determined to be 520℃. The raw CNTs were placed in a muffle furnace and calcined at 520℃ for 0.5 h, then allowed to cool naturally to room temperature. Subsequently, the calcined CNTs were added to a 2.5 mol / L nitric acid solution and stirred at 95℃ for 2 h. After the system cooled naturally, it was centrifuged and washed four times with deionized water. The washed product was placed in a vacuum drying oven and dried under vacuum at 45℃ for 12 h to obtain purified CNTs.

[0070] In a fume hood, 150 mL of 98% concentrated sulfuric acid and 50 mL of 68% concentrated nitric acid were measured. While stirring, the concentrated sulfuric acid was slowly added to the concentrated nitric acid to prepare a mixed acid solution. This mixed acid solution was transferred to a round-bottom flask equipped with a magnetic stirrer, reflux condenser, and tail gas recovery device. 1.0 g of purified CNTs was weighed and slowly added to the mixed acid solution through a long-necked funnel, and dispersed in an ultrasonic cleaner for 30 min. The flask was then placed in an oil bath and refluxed at 55°C for 3 h. After the reaction, the product was washed four times with deionized water by centrifugation and then dried under vacuum at 45°C for 12 h to obtain CNT-COOH. 121 mg of Tris base was weighed and dissolved in approximately 90 mL of deionized water. The pH was slowly adjusted to 8.5 with 1 mol / L HCl, and then the volume was brought to 100 mL to obtain a Tris-HCl buffer solution. 100 mg of CNT-COOH was weighed and added to 60 mL of the above Tris-HCl buffer solution. The mixture was ultrasonically dispersed for 30 min to obtain a uniform black dispersion. 100 mg of dopamine hydrochloride was added to the dispersion, and the mixture was magnetically stirred at 25 °C for 6 h to carry out the PDA coating reaction. After the reaction, the mixture was transferred to a centrifuge tube and centrifuged at 9000 rpm for 10 min. The supernatant was discarded. Deionized water was added to redisperse the precipitate, and the centrifugation and washing were repeated four times until the supernatant was clear. The precipitate was collected, vacuum dried at 45 °C for 15 min, and then gently ground to obtain polydopamine-coated carboxylated carbon nanotubes. The transmission electron microscope image of the polydopamine-coated carboxylated carbon nanotubes prepared in Example 1 is shown below. Figure 2 As shown in the figure, this figure is used to confirm the tubular morphology and dispersion state of CNT-COOH after PDA coating, providing a basis for determining the size and distribution parameters of the reinforcing phase in the subsequent microscopic model.

[0071] (2) Preparation and curing of polydopamine-coated carboxylated carbon nanotubes / EP system

[0072] In this embodiment, bisphenol A type glycidyl ether epoxy resin was used as the main resin, and 1,4-butanediol diglycidyl ether was used as the diluent, with a mass ratio of main resin to diluent of 100:20; isophorone diamine was selected as the curing agent. The resin matrix, curing agent, and polydopamine-coated carboxylated carbon nanotubes were prepared according to a mass ratio of 100:30:0.5. First, the polydopamine-coated carboxylated carbon nanotubes were added to acetone and mechanically stirred at 300 r / min for 10 min, followed by ultrasonic dispersion for 45 min to obtain a uniform dispersion. Then, the resin matrix and curing agent were added sequentially, and the mixture was stirred at 40°C and 300 r / min for 15 min. After depressurization to remove acetone and vacuum degassing, the polydopamine-coated carboxylated carbon nanotube / EP system was obtained. A pure EP control system without polydopamine-coated carboxylated carbon nanotubes was also prepared. The two systems were injected into molds separately and cured in an oven according to the following stepped curing regime: first, the temperature was raised to 80℃ and held for 1 hour, then raised to 120℃ and held for 2 hours, and finally raised to 160℃ and held for 2 hours. After curing, the resin casting samples were naturally cooled to room temperature to obtain the resin casting samples.

[0073] (3) Characterization of mechanical properties and analysis of microstructure

[0074] The tensile and flexural properties of polydopamine-coated carboxylated carbon nanotubes / EP samples and control EP samples were tested according to GB / T 2567-2008. Mechanical parameters such as tensile strength, tensile modulus, elongation at break, and fracture toughness were obtained, and stress-strain curves were plotted. The results are recorded in Table 1. Test results: The tensile strength of the polydopamine-coated carboxylated carbon nanotubes / EP sample was 73.5 MPa, and the tensile modulus was 3326.4 MPa. The tensile strength of the control EP sample was 61.2 MPa, and the tensile modulus was 3025.1 MPa. This indicates that compared with the pure EP system, the tensile strength, tensile modulus, and fracture toughness of the polydopamine-coated carboxylated carbon nanotubes / EP system were all improved.

[0075] Further scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray computed tomography (CT) were used to observe the cross-section and tensile fracture surface of polydopamine-coated carboxylated carbon nanotubes (PCN / EP). The length, diameter, spatial distribution, volume fraction, and aggregation state of the PCN in the resin were analyzed using Avizo technology. Atomic force microscopy (AFM) was used to determine the adhesion properties of the PCN / EP interface. The SEM image of the tensile fracture surface of PCN / EP in Example 1 is shown below. Figure 3 As shown, this illustrates the effect of the dispersion state of the reinforcing phase and the interface bonding of polydopamine-coated carboxylated carbon nanotubes / EP on the fracture morphology.

[0076] (4) Microscopic model construction and simulation analysis

[0077] Based on the experimentally measured size, volume fraction, and dispersion characteristics of polydopamine-coated carboxylated carbon nanotubes (PDCNTs), a random distribution program was developed to generate a randomly and uniformly dispersed PDCNT model in representative volume cells. A three-dimensional microstructure model was then established in ABAQUS software, comprising a resin matrix, a 0.5% PDCNT-coated carboxylated carbon nanotube reinforcing phase, and an interface layer. The resin matrix used C3D8R elements, the PDCNT-coated carboxylated carbon nanotube reinforcing phase used C3D8R and C3D4 elements, and the interface layer used COH3D8 elements. The total number of elements in the model was approximately 8.5 × 10⁴, and the number of nodes was approximately 1.6 × 10⁵. The microstructure model construction, mesh generation, and constraint boundary conditions and load settings for Example 1 are as follows. Figure 4 As shown.

[0078] (5) Material property assignment and model setup

[0079] The resin material properties were assigned based on the experimental mechanical parameters of the control EP system, and the interface layer material properties were assigned based on the atomic force microscopy test results. The boundary conditions were set as follows: one end of the model was completely fixed, and a uniaxial tensile displacement load was applied to the other end.

[0080] (6) Construction of three-dimensional damage constitutive model

[0081] A UMAT user subroutine was written in FORTRAN, using the maximum stress criterion as the damage initiation criterion for the resin matrix, and combining it with fracture energy to control damage evolution; the interface layer adopted a cohesive zone model to describe the interface debonding behavior. Tensile simulation was performed on the microscopic model to obtain stress-strain response, tensile strength, tensile modulus, crack initiation location, crack propagation path, and damage failure mode.

[0082] (7) Simulation analysis and result verification

[0083] The stress peak data obtained from the microscopic model are summarized in Table 1. The results show that the simulation results are in good agreement with the experimental results, indicating that the introduction of uniformly dispersed polydopamine-coated carboxylated carbon nanotubes can effectively improve the stress distribution of the resin matrix, delay crack initiation, inhibit crack propagation, and improve the low-damage sensitivity characteristics and overall mechanical properties of the composite material. The stress distribution cloud diagram corresponding to Example 1 is shown in Table 1. Figure 5 As shown, this is used to display the distribution characteristics of stress transfer, stress concentration, and damage-sensitive areas near the reinforcing phase under tensile load.

[0084] Example 2

[0085] The purification and calcination temperature of CNTs in Example 1 was determined to be 530℃, and the calcination time was 0.5 h, with other conditions remaining unchanged, to obtain purified CNTs. In the preparation and curing process of the polydopamine-coated carboxylated carbon nanotube / EP system, hydantoin epoxy resin was used as the main resin, and 1,4-butanediol diglycidyl ether was used as the diluent, with a mass ratio of main resin to diluent of 100:38; diethyltoluene diamine was used as the curing agent. The resin matrix, curing agent, and polydopamine-coated carboxylated carbon nanotubes were mixed according to a mass ratio of 100:30:0.2 to obtain the polydopamine-coated carboxylated carbon nanotube / EP system. Simultaneously, a pure EP control system without polydopamine-coated carboxylated carbon nanotubes was prepared. The two systems were injected into molds separately and cured in an oven according to the following stepped curing regime: first, the temperature was raised to 90℃ and held for 1 h, then raised to 120℃ and held for 3 h, and finally raised to 150℃ and held for 5 h. After curing, the resin casting samples were naturally cooled to room temperature to obtain the resin casting samples. The tensile and flexural properties of the polydopamine-coated carboxylated carbon nanotube / EP samples and the control EP samples were tested according to GB / T 2567-2008. The tensile strength, tensile modulus, elongation at break, and fracture toughness were obtained, and stress-strain curves were plotted. The results are recorded in Table 1. Test results: The tensile strength of the polydopamine-coated carboxylated carbon nanotube / EP sample was 112.5 MPa, and the tensile modulus was 3658.2 MPa. The tensile strength of the control EP sample was 89.3 MPa, and the tensile modulus was 3265.2 MPa. This study demonstrates that the tensile strength, tensile modulus, and fracture toughness of the polydopamine-coated carboxylated carbon nanotube / EP system are improved compared to the pure EP system. Based on the experimentally measured size, volume fraction, and dispersion characteristics of the polydopamine-coated carboxylated carbon nanotubes, a random distribution program was developed to generate a randomly and uniformly dispersed model of polydopamine-coated carboxylated carbon nanotubes in representative volume cells. A three-dimensional microstructure model containing a resin matrix, a 0.2% polydopamine-coated carboxylated carbon nanotube reinforcing phase, and an interface layer was then established in ABAQUS software. The resin matrix used C3D8 units, the polydopamine-coated carboxylated carbon nanotube reinforcing phase used C3D8R and C3D4 units, and the interface layer used COH3D8 units. The total number of units in the model is approximately 9 × 10^4, and the number of nodes is approximately 2 × 10^5. The resin material properties were assigned based on the experimental mechanical parameters of the control EP system, and the interface layer material properties were assigned based on atomic force microscopy (AFM) results. Boundary conditions were set as follows: one end of the model was completely fixed, and a uniaxial tensile displacement load was applied to the other end. A UMAT user subroutine was written in FORTRAN, using the maximum strain criterion as the damage initiation criterion for the resin matrix, and combining it with fracture energy to control damage evolution; the interface layer used a cohesive zone model to describe the interface debonding behavior.Tensile simulations were performed on the microscopic model to obtain stress-strain response, tensile strength, tensile modulus, crack initiation location, crack propagation path, and damage failure mode. The peak stress data obtained from the microscopic model are summarized in Table 1. The results show that the simulation results are in good agreement with the experimental results, indicating that the introduction of uniformly dispersed polydopamine-coated carboxylated carbon nanotubes can effectively improve the stress distribution of the resin matrix, delay crack initiation, inhibit crack propagation, and improve the low-damage sensitivity characteristics and overall mechanical properties of the composite material.

[0086] Example 3

[0087] In Example 1, vinyl ester resin was used as the main resin, and 1,4-butanediol diglycidyl ether was used as the diluent, with a mass ratio of main resin to diluent of 100:30. Diethyltoluene diamine was used as the curing agent. The resin matrix, curing agent, and polydopamine-coated carboxylated carbon nanotubes were mixed in a mass ratio of 100:30:0.2 to obtain the polydopamine-coated carboxylated carbon nanotube / EP system. A pure EP control system without polydopamine-coated carboxylated carbon nanotubes was also prepared. Both systems were injected into molds and cured in an oven according to the following step-curing regime: first, the temperature was raised to 90°C and held for 1 h; then, the temperature was raised to 130°C and held for 3 h; finally, the temperature was raised to 150°C and held for 5 h. After curing, the mixture was allowed to cool naturally to room temperature to obtain the resin casting sample. The tensile and flexural properties of polydopamine-coated carboxylated carbon nanotubes / EP samples and control EP samples were tested according to GB / T 2567-2008. Mechanical parameters such as tensile strength, tensile modulus, elongation at break, and fracture toughness were obtained, and stress-strain curves were plotted. The results are recorded in Table 1. Test results: The tensile strength of the polydopamine-coated carboxylated carbon nanotubes / EP sample was 95.8 MPa, and the flexural strength was 3426.3 MPa. The tensile strength of the control EP sample was 79.1 MPa, and the flexural strength was 3126.8 MPa. This indicates that compared with the pure EP system, the tensile strength, tensile modulus, and fracture toughness of the polydopamine-coated carboxylated carbon nanotubes / EP system were all improved. A UMAT user subroutine was written in FORTRAN, using the secondary stress criterion as the damage initiation criterion for the resin matrix, and combining it with fracture energy to control damage evolution; the interface layer used a cohesive zone model to describe the interface debonding behavior, while other aspects remained consistent with the examples. Tensile simulations were performed on the microscopic model to obtain stress-strain response, tensile strength, tensile modulus, crack initiation location, crack propagation path, and damage failure mode. The peak stress data obtained from the microscopic model are summarized in Table 1. The results show that the simulation results are in good agreement with the experimental results, indicating that the introduction of polydopamine-coated carboxylated carbon nanotubes can effectively improve the stress distribution of the resin matrix, delay crack initiation, inhibit crack propagation, and improve the low-damage sensitivity characteristics and overall mechanical properties of the composite material.

[0088] Comparative Example 1

[0089] In the microscopic model construction and simulation analysis of Example 1, a random distribution program was written to generate a polydopamine-coated carboxylated carbon nanotube aggregation model in a representative volume element. A three-dimensional microscopic model containing a resin matrix, a 0.5% polydopamine-coated carboxylated carbon nanotube reinforcing phase, and an interface layer was then established in ABAQUS software. Other aspects remained consistent with the Example 1. Tensile simulations were performed on the microscopic model to obtain stress-strain response, tensile strength, tensile modulus, crack initiation location, crack propagation path, and damage failure mode. The peak stress data obtained from the microscopic model are summarized in Table 1. The results show that the introduction of polydopamine-coated carboxylated carbon nanotubes with aggregation behavior creates stress concentration points, accelerates crack initiation and propagation, and significantly reduces the overall mechanical properties of the composite material.

[0090] Table 1 Experimental test results and finite element prediction results

[0091]

[0092] The results of the above embodiments show that the introduction of uniformly dispersed polydopamine-coated carboxylated carbon nanotubes can effectively improve the stress distribution of the resin matrix, delay crack initiation, inhibit crack propagation, and improve the low damage sensitivity characteristics and overall mechanical properties of the composite material.

Claims

1. A method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites, characterized in that, Includes the following steps: (1) Preparation of polydopamine-coated carboxylated carbon nanotubes: (a) Purification of CNTs: CNTs were placed in a muffle furnace and calcined at 480-550°C for 0.5-1 hour. After natural cooling, the calcined CNTs were mixed with 2.5-3.0 mol / L nitric acid solution and stirred at 90-100°C for 2-3 hours. After natural cooling, the mixture was centrifuged. The product was washed 3-5 times with deionized water and dried in a vacuum drying oven at 40-50°C for 10-15 hours to obtain purified CNTs. (b) Preparation of CNT-COOH: Under ventilation conditions, 150 mL of concentrated sulfuric acid was slowly added to 50 mL of concentrated nitric acid while stirring with a glass rod to obtain a mixed acid solution. The mixed acid solution was transferred to a 100 mL round-bottom flask equipped with a magnetic stirrer, reflux condenser and tail gas recovery device. 1.0 g of purified CNTs was weighed and slowly added to the mixed acid solution through a long-necked funnel. After ultrasonic dispersion for 30 minutes, the flask was placed in an oil bath and refluxed and stirred at 50-60°C for 3-4 hours. Then, the flask was washed 3-4 times by centrifugation with deionized water and dried in a vacuum drying oven at 40-50°C for 10-15 hours to obtain CNT-COOH. (c) Preparation of polydopamine-coated carboxylated carbon nanotubes: Weigh 100-150 mg of Tris base, dissolve it in 80-100 mL of deionized water, slowly adjust the pH to 8.5 with 1 M HCl, and bring the volume to 100 mL to obtain Tris-HCl buffer; weigh 100 mg of CNT-COOH and add it to 50-80 mL of Tris-HCl buffer, sonicate for 30 minutes to obtain a uniform black dispersion; weigh 100 mg of dopamine hydrochloride and add it to the black dispersion; perform PDA coating reaction by magnetic stirring at 15-30℃ for 6-8 hours; after the reaction, transfer the mixture to a centrifuge tube and centrifuge at 8000-10000... Centrifuge at rpm for 10-15 min, discard the supernatant, disperse the precipitate with deionized water by ultrasonication and repeat centrifugation 3-5 times until the supernatant is clear, collect the precipitate, place it in a vacuum drying oven and dry at 40-50°C for 10-15 h, and grind it to obtain polydopamine-coated carboxylated carbon nanotubes. (2) Configuring a polydopamine-coated carboxylated carbon nanotube / EP system Weigh the polydopamine-coated carboxylated carbon nanotubes prepared in step (1), add them to the acetone solution according to the preset addition amount, stir for 5 to 10 min under mechanical stirring at 200 to 500 r / min, and then perform ultrasonic dispersion treatment for 30 to 60 min. Then add the resin matrix and curing agent to the dispersion in sequence, and continue stirring for 10 to 20 min under the conditions of 25 to 80 ℃ and 200 to 500 r / min. Remove the acetone by vacuum to obtain resin systems with different polydopamine-coated carboxylated carbon nanotube contents. As a control, prepare a pure EP system containing only resin matrix and curing agent at the same time. Finally, place each group of resin systems in an oven and cure according to the step curing regime to obtain polydopamine-coated carboxylated carbon nanotube / EP composite material samples with different polydopamine-coated carboxylated carbon nanotube distribution characteristics. (3) Performance characterization of polydopamine-coated carboxylated carbon nanotubes / EP The microstructure of polydopamine-coated carboxylated carbon nanotube / EP composites with different polydopamine-coated carboxylated carbon nanotube contents prepared in step (2) and the control samples of the pure EP system were characterized by non-destructive testing. Information such as the particle size, distribution position, aggregation degree and orientation characteristics of polydopamine-coated carboxylated carbon nanotubes in the resin matrix were obtained, and the dispersion uniformity was quantitatively evaluated by image analysis. At the same time, the mechanical properties of each group of samples were tested to obtain the corresponding mechanical property parameters. Furthermore, the adhesion performance of polydopamine-coated carboxylated carbon nanotubes to the EP matrix interface was determined by scanning probe microscopy, which provides a parameter basis for subsequent microscopic model construction and damage analysis. (4) Construction of the microstructure model of polydopamine-coated carboxylated carbon nanotubes / EP Based on the actual size and spatial distribution characteristics of polydopamine-coated carboxylated carbon nanotubes obtained in step (3), a program was written to realize the microscopic modeling of polydopamine-coated carboxylated carbon nanotubes in the resin matrix. Uniform dispersion microscopic models and agglomeration dispersion microscopic models under different polydopamine-coated carboxylated carbon nanotube contents were established respectively. A microscopic model containing resin, polydopamine-coated carboxylated carbon nanotubes and polydopamine-coated carboxylated carbon nanotubes / EP interface was created in ABAQUS software. (5) Material property assignment and model setup Based on the mechanical property parameters of the control sample obtained in step 3), the material properties of the resin component in the micro model are assigned. Based on the adhesion properties of the polydopamine-coated carboxylated carbon nanotubes and the EP interface obtained in step 3), the material properties of the polydopamine-coated carboxylated carbon nanotubes / EP interface in the micro model are assigned. The micro model created in step (4) is meshed, and the constraints, boundary conditions and loads of the micro model are set. (6) Construction of three-dimensional damage constitutive model Based on the three-dimensional failure criteria and fracture energy evolution method, a FORTRAN user-defined UMAT subroutine was written to construct a three-dimensional damage constitutive model of resin, polydopamine-coated carboxylated carbon nanotubes and interface phases, so as to realize the initial damage determination, stiffness degradation and crack propagation analysis of polydopamine-coated carboxylated carbon nanotubes / EP. (7) Simulation analysis and result verification The tensile strength and tensile modulus of the micro-models established under different polydopamine-coated carboxylated carbon nanotube contents and dispersion degrees were analyzed and compared with the tensile results obtained from experimental tests. This verifies the influence of the dispersion state and content of polydopamine-coated carboxylated carbon nanotubes on the damage sensitivity characteristics and damage evolution behavior of the resin system. Furthermore, the damage evolution process and failure mode of the material under different conditions were analyzed.

2. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The purification and calcination temperature of the CNTs was determined by thermogravimetric analysis (TGA). The TGA was performed on the CNTs in an air atmosphere to obtain the TGA curve. The first derivative of the TGA curve was performed based on temperature to determine the temperature window between the oxidation weight loss range of the amorphous carbon doped in the CNTs and the decomposition temperature of the CNTs. The purification and calcination temperature range of the CNTs was determined to be 480-550℃, preferably 500-530℃.

3. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The mixed acid solution is composed of concentrated sulfuric acid and concentrated nitric acid, wherein the mass fraction of concentrated sulfuric acid is 95%-98%, the mass fraction of concentrated nitric acid is 65%-68%, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 5:2-5:

3.

4. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The resin matrix is ​​composed of a main resin and a diluent. The resin matrix is ​​liquid at 10-30°C. The main resin is preferably a compound of one or more of the following: glycidyl ethers, glycidyl esters, glycidyl amines, hydantoin epoxy resins, vinyl resins, phenolic resins, bismaleimide resins, cyanate ester resins, polyimide resins, and polyurethanes. The diluent is preferably alkylene glycidyl ether, 1,6-hexanediol diglycidyl ether, butyl glycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, phenyl glycidyl ether, benzyl glycidyl ether, and polypropylene glycol diglycidyl ether. The curing agent is a compound of one or more of glycidyl ethers, wherein the mass ratio of the main resin to the diluent is 100:10-30; the curing agent is liquid at 10-30°C, preferably a compound of one or more of phthalic anhydride, dimethylthiotoluene diamine, isophorone diamine, diethyltoluene diamine, triethylenetetramine, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and methylnadic anhydride, wherein the mass ratio of the resin matrix, the curing agent, and the polydopamine-coated carboxylated carbon nanotubes is 100:10-40:0.1-0.

8.

5. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The stepped curing process includes: a) first heating to 60-100 ℃ and holding for 0.5-2 h; b) then heating to 100-140 ℃ and holding for 1-5 h; c) finally heating to 150-180 ℃ and holding for 1-5 h.

6. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The mechanical properties parameters include tensile strength, tensile modulus, elongation at break, Poisson's ratio, fracture toughness, and other mechanical property tests of polydopamine-coated carboxylated carbon nanotubes / EP, and the stress-strain curves of polydopamine-coated carboxylated carbon nanotubes / EP are obtained.

7. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The non-destructive testing includes metallographic microscopy, transmission electron microscopy, scanning electron microscopy, atomic force microscopy, and X-ray computed tomography (CT) observation of the cross-section of polydopamine-coated carboxylated carbon nanotubes (EP), as well as metallographic microscopy, transmission electron microscopy, scanning electron microscopy, and X-ray computed tomography observation of the tensile fracture surface of polydopamine-coated carboxylated carbon nanotubes (EP). The image analysis methods include depth-of-field rendering and Avizo rendering techniques. The particle size and dispersion state include the length and diameter of polydopamine-coated carboxylated carbon nanotubes, as well as their spatial distribution, volume fraction, and aggregation state within the polydopamine-coated carboxylated carbon nanotubes (EP).

8. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, In the microscopic model, taking the resin matrix as a reference, at least five groups of polydopamine-coated carboxylated carbon nanotubes are set with a dispersion mass fraction of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, and 0.8%, and the microscopic distribution of polydopamine-coated carboxylated carbon nanotubes in the resin matrix under different mass fraction conditions is modeled by writing a program.

9. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, In the microscopic model, the preferred mesh type for the resin is C3D8 or C3D8R; the preferred mesh types for polydopamine-coated carboxylated carbon nanotubes are C3D8, C3D8R, C3D4, and C3D6; the polydopamine-coated carboxylated carbon nanotube / EP interface is characterized by zero-thickness cohesive units, thin-layer interface units, or equivalent interface layers to represent the interfacial damage evolution behavior between the polydopamine-coated carboxylated carbon nanotubes and the resin matrix, with the interface layer preferably being a COH3D8 mesh type. The microscopic model contains 1,000-300,000 units and 50,000-800,000 nodes.

10. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The constraints, boundary conditions, and loads include setting periodic boundaries and applying uniaxial tensile displacement loads at control points.

11. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The three-dimensional failure criteria include one or more of the maximum strain criterion, maximum stress criterion, secondary stress criterion, and linear evolution methods based on the definition of fracture energy. The maximum stress criterion and maximum strain criterion are used to define the initial failure in the polydopamine-coated carboxylated carbon nanotube / EP model. The expression for the maximum strain criterion is as follows: ; Failure occurs if any of the conditions are met. If the material is considered isotropic, it can be further simplified to: or ; in The principal strains represent the three principal directions of the material. This represents the ultimate tensile strain in the corresponding direction. This represents the ultimate compressive strain in the corresponding direction. Represents the maximum principal strain. Represents the minimum principal strain. Represents the ultimate tensile strain of a material. Represents the ultimate compressive strain of the material; The maximum stress criterion is expressed as follows: ; Failure occurs if any of the conditions are met. If the material is considered isotropic, it can be further simplified to: or ; in Represents the three principal stresses of the material. Represents the ultimate tensile strength in the three principal directions. Represents the ultimate compressive strength in the three principal directions. Represents the maximum principal stress. Represents the minimum principal stress. Represents the ultimate tensile strength of a material. Represents the ultimate compressive strength of the material; A secondary stress criterion is used to define the crack initiation criterion in the crack propagation region of the polydopamine-coated carboxylated carbon nanotube / EP model. The principal stress form of the secondary stress criterion is expressed as follows: ; The failure condition is: ; The stress component form of the secondary stress criterion is expressed as follows: ; in, Represents the Von Mises equivalent stress. Represents the three principal stresses of the material. Representing three normal stress components, Representing three shear stress components, Represents the yield strength of the material; A linear evolution method based on the definition of fracture energy is used to define the crack propagation evolution law in the crack propagation region of the polydopamine-coated carboxylated carbon nanotube / EP model, wherein the criterion for crack propagation is: ; Where G is the energy release rate per unit crack surface. G is the energy release rate per unit crack area. C It is the critical fracture energy of the material.

12. The method for evaluating the damage sensitivity of polydopamine-coated carboxylated carbon nanotube-reinforced resin matrix composites according to claim 1, characterized in that, The custom UMAT subroutine, based on the selected failure criteria and performance degradation model, compiles a performance degradation program for polydopamine-coated carboxylated carbon nanotubes / EP. It stores the calculated material performance parameters and failure coefficients as state variables, comprehensively considering various damage mechanisms of polydopamine-coated carboxylated carbon nanotubes during uniaxial tensile testing, including microscopic damage modes such as resin matrix cracking and debonding of polydopamine-coated carboxylated carbon nanotubes from the resin. The simulated tensile strength, tensile modulus, crack initiation location, crack propagation path, and damage failure modes are compared with experimental results to evaluate the effects of polydopamine-coated carboxylated carbon nanotube content and dispersion state on the low-damage sensitivity characteristics, interfacial toughening effect, and mechanical property improvement of the resin composite material.